Ejecución presupuestaria en el Gad parroquial San Juan en el período 2022. - Naranjo Pluas, Esther Andreina (2023)
The case study was carried out in the Parochial Decentralized Autonomous Government of San Juan, where the management of compliance with the institutional budget in the period 2022 was investigated. Therefore, the general objective of the study was established to evaluate the budget execution of the Autonomous Government Decentralized Parish of San Juan, period 2022, with the intention of establishing the main weaknesses of the institution with respect to the planning of the institution. While the methodological framework is made up of the following components: the methodology is a mixed approach, whose types of research are documentary and field. On the other hand, the inductive method was applied, supported by techniques, interviews and documentary analysis. The interview was directed to the treasurer of the institution and the documentary analysis was carried out on the documentation related to budget execution, where the results were obtained that the income budget presented a deviation of 78% and the deviation in the execution of expenses was 80%, where the “Public Works” account is the most affected. Regarding the income budget, only 22% of what was planned was executed; while in the expenses group the execution was 10%. Therefore, it is concluded that budget management has not been optimal.